English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

15 answers

9

2007-03-09 03:56:26 · answer #1 · answered by Hk 4 · 1 0

Basic Algebra, got to love it. All you have to do is plug in your values of A, and B. You see how there is no space between the a and 2 or the 2, a, and b. Basically that means that all those values will just be multiplied. Here is an example:
If a= -4 and b= 7, what is the value of a2 + 2ab + b2?

Here is what the solution would look like:
(-4)2 + 2 (-4) (7)+ (7)2
A negative times a positive gives you a negative.
So, -8(2) = -16 and 2(-4)= -8(7)=-56
Then, (-16) + (-56) + 14 = -72 + 14
Which is basically a subtraction problem, and your answer would have to be negative because 72 is further away from zero on the number line than 14:
Answer: -58

Hope this helps!

2007-03-09 12:07:34 · answer #2 · answered by topcat 2 · 0 1

You substitute the values of a and b into the equation
(-2)^2+2(-2)(5)+5^2
=4-20+25
= 9

2007-03-09 11:44:42 · answer #3 · answered by Forsaken 2 · 1 0

= (-2)² + 2(- 2 x 5) + 5²
= 4 - 20 + 25
= 9

2007-03-09 11:42:56 · answer #4 · answered by Como 7 · 1 0

9

2007-03-09 12:30:42 · answer #5 · answered by Alias 2 · 0 0

a^2 + 2ab + b^2.

Instead of blindly just plugging in a = -2 and b = 5, let's change the form of the above by factoring it.

(a + b)(a + b)

Now, let's plug in a = -2, b = 5. The result is less operations (less multiplying and adding), giving us

(-2 + 5)(-2 + 5)

(3)(3)

9

2007-03-09 11:40:46 · answer #6 · answered by Puggy 7 · 1 0

a^2+2ab +b^2= (a+b)^2 = (-2+5)^2 = 3^2 = 9

2007-03-09 11:54:08 · answer #7 · answered by ironduke8159 7 · 0 0

(-2)^2+2*-2*5+5^2= 4-20+25 = 9


Another way to think of it is that the equation can be rewritten as (a+b)^2=(5-2)^2=3^2=9

2007-03-09 11:42:55 · answer #8 · answered by LMS 3 · 1 0

its 9...i dont think its 14 because you have to do the mulitply first than subtract...for example

2 a b
2(-2)(5)
you would do (-2)(5) first
and then 2(-10)

also negative times a negative makes the answer positive
for example -2 (squared) gives a positive 4.

2007-03-09 12:04:52 · answer #9 · answered by Its me again 5 · 0 1

assuming that's a^2,

plug in

(-2)^2 +2(-10) + (5)^2

4-20+25=9

2007-03-09 11:42:37 · answer #10 · answered by flkasdjflkasdj;lrf 3 · 1 0

fedest.com, questions and answers